The Efficacy Of Modified Anti Tension Tape (HypafixÂ®) As A Prevention Of Hypertrophic Scar In Facial Region Measured By Vancouver Scar Scale (VSS) - Laksono, Gerardo AK; Tahalele, Paul L; Anggowarsito, Jose L; Joseph, Herman (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction : Every wound healing process always leaves a scar, hypertrophic scar is a result of abnormal wound healing. Many therapeutic modalities have been discovered that can be used to deal with abnormal scar, but it?s expensive. A modified Anti Tension tape can be used as a modality for hypertrophic scar prevention therapy with an affordable price Aim : The purpose of this study is to find out the effect of application modified anti tension tape (Hypafix®) with the scar quality measured by Vancouver Scar Scale . Methods : This is an observational analytic study using primary data and Cohort study method. The sample in this study were 32 people divided into 2 groups treatment and control group with Non-probability - Consecutive sampling as a data collection techniques. The statistical test used is chi square. Results : From 16 samples treatment group, 14 samples have a good scar quality, 2 samples have a medium/bad scar quality. From 16 samples control group, 5 samples have a good scar quality, 11 samples fall into medium/bad scar quality. Chi square score p= 0,004 Conclusion : There is a positive significant effect between the application modified anti tension tape (Hypafix®) with the scar quality measured by Vancouver Scar Scale